Regulatory T-Cells at the Interface between Human Host and Pathogens in Infectious Diseases and Vaccination - Boer, Mardi C.; Joosten, Simone A.; Ottenhoff, Tom H. M. (Frontiers in Immunology, 2015)
Regulatory T-cells (Tregs) act at the interface of host and pathogen interactions in human infectious diseases. Tregs are induced by a wide range of pathogens, but distinct effects of Tregs have been demonstrated for different pathogens and in different stages of infection. Moreover, Tregs that are induced by a specific pathogen may non-specifically suppress immunity against other microbes and parasites. Thus Treg effects need to be assessed not only in homologous but also in heterologous infections and vaccinations. Though Tregs protect the human host against excessive inflammation, they probably also increase the risk of pathogen persistence and chronic disease, and the possibility of disease reactivation later in life. Mycobacterium leprae and Mycobacterium tuberculosis, causing leprosy and tuberculosis (TB), respectively, are among the most ancient microbes known to mankind, and are master manipulators of the immune system towards tolerance and pathogen persistence. The majority of mycobacterial infections occurs in settings co-endemic for viral, parasitic and (other) bacterial coinfections. In this paper we discuss recent insights in the activation and activity of Tregs in human infectious diseases, with emphasis on early, late and non-specific effects in disease, coinfections and vaccination. We highlight mycobacterial infections as important models of modulation of host responses and vaccine induced immunity by Tregs.